The Providing Of Covid-19 Education On The Knowledge And Anxiety Levels Of High School Students - Nurul Devi Ardiani; Maula Mar'atus Solikhah (Poltekkes Kemenkes Surakarta, 2022)
Background: The lack of knowledge about COVID-19 could lead to various types of speculation about the Coronavirus spread, causing anxiety in the public and diminishing the body's immune system. Education about COVID-19 is a method to enhance school students' knowledge because school clusters are one of the contributors to the increasing number of COVID-19 in Indonesia. Methods: The research method adopted was quasi-experimental, with a pre-and post-test without control on 72 students. The students were selected randomly through the coordination of the student affairs teacher involved in this study. The online g-form was used twice to collect data. Pre-education data collection was conducted a day before the implementation of education, and then the evaluation of post-education was implemented several days after performing education. Pre- and post-education used two (2) questionnaires on knowledge and anxiety. Data were analyzed by using the Wilcoxon test Results: The results of the Wilcoxon test on the pre- and post-education variables on students' knowledge presented a value of -4.938 (p = 0.000) with a p-value of <0.05. Therefore, it was concluded that there was an effect of COVID-19 education on students' knowledge. The results of the Wilcoxon test on the pre-and post-education variables on student anxiety showed a value of -3.587 (p = 0.000) with a p-value of <0.05. Conclusion: There was an effect of COVID-19 education on the student's knowledge and anxiety levels. The results of this study are expected to provide benefits for respondents, especially in diminishing anxiety by increasing their knowledge of COVID.